Exploration of Passing Training Methods in Futsal Games: Review Study - Suwandi, Satrya; Fernando, Ricky (Universitas Majalengka, 2025)
Futsal players are a popular sport and are widely loved by teenagers today. The purpose of this study is to determine the method of passing training on ball passing skills in futsal sports. The method used in this study is a literature review by analyzing the method of passing training in futsal games. Seven articles in the form of research journals that have been analyzed by the author related to the title of the writing, namely the relationship between passing training methods and passing skills in futsal players, so this literature review has the conclusion that there is a relationship between passing training methods and passing skills in futsal players.